Benchmarking the nutrient composition and labelling practices of dry or instant cereals for older infants and young children across seven Southeast Asian countries - Eleonora Bassetti; Jessica Blankenship; Jessica M. White; Lara Sweet; Diane Threapleton; Alissa M. Pries (Wiley, 2023)
Abstract In Southeast Asia, the increasing availability of commercially produced complementary foods (CPCF), including dry or instant cereals (CPCF cereals), has been noted, however, concerns exist around their nutrient profile and labelling practices. This 2021 study assessed the nutrient composition, labelling practices, and micronutrient content of CPCF cereals sold in the capital cities of seven Southeast Asian countries: Phnom Penh (Cambodia), Jakarta (Indonesia), Manila (Philippines), Bangkok (Thailand), Vientiane (Lao PDR), Hanoi (Vietnam), and Kuala Lumpur (Malaysia). The study adapted a nutrient profiling model from the WHO Regional Office for Europe to determine the proportion of products suitable for promotion for older infants and young children. Micronutrient content of fortified CPCF cereals was assessed against fortification levels specified in the Codex Alimentarius guideline for formulated complementary foods. Of the 484 products assessed, 184 (38.0%) met all nutrient composition requirements. Around one‐third of CPCF cereals contained added sugars and/or sweeteners (37.2%) and high levels of sodium (28.9%). None of the CPCF cereals met all labelling requirements, primarily due to the presence of inappropriate claims on the labels. Most fortified CPCF cereals contained adequate amounts of critical micronutrients, such as calcium, iron, zinc, vitamin A, and vitamin D. However, rates of fortification varied across the seven countries, and almost a third (30.8%) of CPCF cereals were not fortified with any micronutrients. To support the appropriate promotion of CPCF in the region, Southeast Asian countries need to strengthen and enforce national binding legal measures, including national standards for the composition, labelling, and fortification of CPCF cereals.